Analysis of The Impact Financial Action Task Force On Money Laundering and Terrorism Financing?(FATF) On The Supervision of Money Laundering and Terrorism Financing Crimes In Indonesia - Winardi Ginting; Margaretha Hanita; Stanislaus Riyanta (Pelopor Publikasi Akademika, 2024)
This research is based on the fact of Indonesia's great efforts in combating money laundering and terrorism financing practices that brought Indonesia to be recognized as the 40th member of the FATF. The purpose of this study is to analyze the threats, vulnerabilities and risks of money laundering and terrorism financing crimes and describe the potential impact of Indonesia's involvement as a member of the FATF on the prevention, supervision and enforcement of these crimes. Using a descriptive qualitative approach, this study uses secondary data from related institution documents and a number of previous research journals as a basis for analyzing the problem under study. The results showed that money laundering and terrorism financing crimes are very high when viewed from the trend in the number of crackdowns in recent years. In addition, the vulnerability related to several problems that are still faced such as weak declarations on carrying cash, large objects of supervision, problems with data input in the system, not standardized supervisory infrastructure, limited authority of the DGT and not integrated reporting applications among related institutions. The potential impact of Indonesia's involvement as a member of the FATF on the prevention, supervision and enforcement of crimes is to increase the credibility of the country's economic management as the main investment attraction. Safeguarding Indonesia's international political interests in influencing international policy in accordance with Indonesia's national interests. And become a catalyst that encourages or